Financial Distress Analysis as Early Warning System on Halal Tourism Industries: Case Study during Covid-19 Pandemic Era - Puspita, Nindy Akbar Lintang; Pambekti, Galuh Tri; Khoirunisa, Kharisa Rachmi (Faculty Of Islamic Economics and Business, 2024)
Purpose: To know whether there is a difference in the level of accuracy between the Altman, Zmijewski, and Springate models in analyzing financial distress in halal tourism industries during the COVID-19 pandemic.Design / methodology / approach: A quantitative method with a comparative descriptive approach.Research Findings: There are different levels of accuracy that prove that there is a difference in the level of accuracy between the Altman, Zmijewski and Springate models in analyzing financial distress tourism industries during the COVID-19 pandemic.Contribution / Originality / Novelty: It can practically assist company management in understanding financial distress analysis and help investors, both individual and institutional investors, to see the potential for company bankruptcy as a consideration in investing. Tujuan Penelitian: Untuk mengetahui apakah terdapat perbedaan tingkat akurasi antara model Altman, Zmijewski, dan Springate dalam menganalisis financial distress pada industri pariwisata halal pada masa pandemi COVID-19.Desain / metodologi / pendekatan: Metode kuantitatif dengan pendekatan deskriptif komparatif.Temuan Penelitian: terdapat perbedaan tingkat akurasi membuktikan bahwa terdapat perbedaan tingkat akurasi antara model Altman, Zmijewski dan Springate dalam menganalisis industri pariwisata financial distress pada masa pandemi COVID-19.Kontribusi / Orisinalitas / Kebaruan: Secara praktis dapat membantu manajemen perusahaan dalam memahami analisis kesulitan keuangan dan membantu investor, baik investor individu maupun institusi, untuk melihat potensi kebangkrutan perusahaan sebagai pertimbangan dalam berinvestasi.